indonesia Integration of Social, Religious and Cultural Relations in Lomban Kupatan Sungai Tayu Tradition - Ulin Nihayah Ulin Nihayah (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2021)
Culture is the unifier in society in multicultural conditions that leads breaking the Indonesian unity. Javanese culture is very attached to rituals and traditions that are passed from generation to generation. The procession of cultural customs is carried out by the community through traditional ceremonies, which can unite all elements in the society. This study uses a qualitative approach based on literature study. The analysis results conclude that in the Larung Sesaji and Lomban Kupatan Tayu River procession, there are sacred and profane concepts proposed by Emile Durkheim, as a unit of the Tayu community as actor and supported by tourists outside of the city of Tayu. Furthermore, the Lomban procession examines that the characteristics of social integration in the community with the interaction, identification, cooperation, integration and assimilation that have been manifested in the Kupatan tradition.